ANALISIS TEORI WACANA VAN DIJK TERHADAP BERITA “SEKITAR 4 RIBU PEMUDIK POSITIF CORONA, SATGAS COVID 19: MASIH BERPOTENSI MENINGKAT!!” - Algina Shofiyatul Husna; Dadang S. Anshori; Jatmika Nurhadi (STKIP Siliwangi, 2021)
This study discusses discourse analysis of news texts entitled ”Sekitar 4 Ribu Pemudik Positif Corona, Satgas Covid-19: Masih Berpotensi Meningkat!” which was published on May 13, 2021 on the official website newsetup.kontan.co.id. The purpose of this study was to find out whether the news text entitled “Sekitar 4 Ribu Pemudik Positif Corona, Satgas Covid-19: Masih Berpotensi Meningkat!” contains the elements contained in van Dijk's discourse theory, then qualifies the results according to the predetermined categories. This study uses a qualitative descriptive method with a discourse analysis approach to the Teun A. van Dijk model. The discourse theory divides the structure of the text into three levels, namely the macro structure, super structure, and micro structure. The result was found that the news text entitled “Sekitar 4 Ribu Pemudik Positif Corona, Satgas Covid-19: Masih Berpotensi Meningkat!” does not meet the elements text contained in van Dijk's discourse theory. The elements contained in the news text analyzed include coherence, conditional coherence, sentence form, pronouns, setting, details, intent, lexicon, and graphics. In addition, it can be concluded that journalists show a neutral attitude towards the pros and cons that occur as a result of the prohibition against going home through the published news.